Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas terhadap Harga Saham pada Perusahaan Sub Sektor Perdagangan Eceran yang Terdaftar di BEI - Retno Anggita Putri; R.A. Suwaidi (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research was a purpose to provide empiricial evident about liquidity, solvability, and profitability on stock prices. Current Ratio, Debt to Equity Ratio, and Return on Equity are the independent variables in this variable, while stock price is the dependent variable. Retail trading sub-sector companies that are active, traded, and listed in BEI 2015 to 2019 are the subjects of this study. Purposive sampling was used, which meant that the sampling was done based on a set of criteria. A quantitative technique was applied in the investigation. Secondary data was used, which included information from firm annual reports, observations, and paperwork. Multiple linear regression was employed to analyze the data. The findings of this study show that liquidity gains and solvency ratios have no impact on stock prices, however profitability ratios have an impact on stock prices in BEI's retail trade sub-sector enterprises.